Effect of Cigarette Smoke on Bronchial Reactivity - JL Wright; J-P Sun; S Vedal; A Churg (Canadian Respiratory Journal)
OBJECTIVE: To compare the effects of a brief low level exposure to cigarette smoke in rats with known low (Sprague-Dawley) and high (Fisher) airway responsiveness, to test the hypothesis that airways reactivity influences the severity or duration of pulmonary function alterations after cigarette smoke exposure.